Answer:
12
Step-by-step explanation:
N:S:G
6:2:1
Nick gets 30 more sweets than Gavyn, therefore we can say that.
![6x=x+30\\5x=30\\x=6](https://tex.z-dn.net/?f=6x%3Dx%2B30%5C%5C5x%3D30%5C%5Cx%3D6)
As Sarah gets twice the amount of sweets that Gavyn does.
![2(6)=12](https://tex.z-dn.net/?f=2%286%29%3D12)
Answer:
4.5
Step-by-step explanation:
The equation of the transformation of the exponential function <em>y</em> = 2ˣ in the form <em>y</em> = A·2ˣ + k, obtained from the simultaneous found using the points on the graph is <em>y</em> = (-2)·2ˣ + 3
<h3>What is an exponential equation?</h3>
An exponential equation is an equation that has exponents that consists of variables.
The given equation is <em>y</em> = 2ˣ
The equation for the transformation is; <em>y</em> = A·2ˣ + k
The points on the graphs are;
(0, 1), (1, -1) and (2, -5)
Plugging the <em>x </em>and <em>y</em>-values to find the value <em>A</em> and <em>k</em> gives the following simultaneous equations;
When <em>x</em> = 0, <em>y</em> = 1, therefore;
1 = A·2⁰ + k = A + k
1 = A + k...(1)
When <em>x</em> = 1, <em>y</em> = -1, which gives;
-1 = A·2¹ + k
-1 = 2·A + k...(2)
Subtracting equation (1) from equation (2) gives;
-1 - 1 = 2·A - A + k - k
-2 = A
1 = A + k, therefore;
1 = -2 + k
k = 2 + 1 = 3
k = 3
Which gives;
y = -2·2ˣ + 3 = 3 - 2·2ˣ
Learn more about the solutions to simultaneous equations here:
brainly.com/question/26310043
#SPJ1
By paying attention in school
Answer:
71
Step-by-step explanation:
Remember to always follow PEMDAS as well as the left -> right rule. While you do not need PEMDAS for this expression specifically, it is always good to know it. PEMDAS is the order of operations:
PEMDAS =
Parenthesis
Exponents (& Roots)
Multiplication
Division
Addition
Subtraction
-----------------------------------------------------------------------------------------------------
First, solve the parenthesis:
(6 - 3) = 3
Next, simplify, by adding:
36 + 32 + 3 =
68 + 3 = 71
71 is your answer.
~